Opportunities and challenges for the use of cleaner production to reduce water consumption in Brazilian sugar-energy plants - Gonçales Filho, Manoel; Nunhes, Thais Vieira [UNESP]; Barbosa, Luis César Ferreira Motta [UNESP]; de Campos, Fernando Celso; de Oliveira, Otávio José [UNESP] (Elsevier, 2018)
Water is a finite and scarce resource that has gained importance in the global economic scenario. The sugar-energy plants use water intensively for the development of their activities, which demands that their top management incorporate actions to reduce or eliminate the use of this resource. In Brazil, the annual production of sugarcane is over 650 million tons/year and, on average, 1.18 m³ of water is consumed per ton of processed sugarcane. Given this, it is important to look for alternatives that allow the reduction of the volumes of water collection and use in Brazilian sugar-energy plants. The objective of this paper is to identify opportunities and challenges for using Cleaner Production (CP) to reduce water consumption in brazilian sugar-energy plants. To carry out this study, four case studies were conducted, whose data collection was based on semi-structured interviews with plant managers, document analysis and on-site visits. The case studies were analyzed individually, and then their cross-analysis were conducted in order to understand and present them in a transversal way to all the companies studied. Among the opportunities for improvement identified are the use of dry cleaning system for sugarcane cleaning, the classification and analysis of effluents, the analysis of the water consumption in the processes and the use of the system of concentration of vinasse. The main scientific contribution of this study is the systematization of CP interventions to reduce water consumption in sugar-energy plants, which expands the existing theory. The results of this work revealed that the opportunities and challenges presented may help companies to reduce considerably the volume of water used in their production systems, thus contributing to the preservation of the environment and the development of future generations.